2020
DOI: 10.1021/acsami.0c20211
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulated “Breathing” Vesicle with Inversed Supramolecular Chirality

Abstract: Though phospholipids possess chiral centers, their chiral aggregation within bilayer cell membranes has seldom been referred and recognized. Insight into the chirality at higher levels in artificial molecular bilayer assemblies such as vesicles or liposomes is important to better understand biomembrane functions. In this work, we illustrate the fabrication of chiral vesicles with photoresponsive supramolecular chirality and structural transformation property. Cholesterol was conjugated to azobenzene via differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Moreover, besides the assembly‐disassembly process, photoisomerization of azobenzene may also cause the inversion of supramolecular chirality. In 2021, Xing et al [24] . innovatively designed a chiral vesicle composed of cholesterol‐coupled azobenzene.…”
Section: Non‐polarized Light Driven Supramolecular Chiralitymentioning
confidence: 99%
“…Moreover, besides the assembly‐disassembly process, photoisomerization of azobenzene may also cause the inversion of supramolecular chirality. In 2021, Xing et al [24] . innovatively designed a chiral vesicle composed of cholesterol‐coupled azobenzene.…”
Section: Non‐polarized Light Driven Supramolecular Chiralitymentioning
confidence: 99%
“…As a more efficient strategy to achieve controllable and inverted handedness, supramolecular co-assembly offers a convenient platform to precisely regulate the arrangement of programmable building blocks via noncovalent interactions (π–π stacking, hydrogen bonds, hydrophobic interactions, van der Waals interactions, and metal coordination). On account of the dynamic and reversible features of noncovalent interactions, the supramolecular chirality and CPL properties of artificial supramolecular co-assembly systems can be rationally modulated by various stimuli, such as light irradiation, chiral or achiral additives, stoichiometry, assembling rate, and metal ions. Liu’s group reported that the chirality of cinnamic acid derivatives could be inverted with morphology changed from superhelices to nanokebabs upon ultraviolet light irradiation . Feng’s group fabricated l-phenylalanine hydrogels with controlled supramolecular chirality by cooperating with metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…Different from complete structure dissociation, the cell organelles exchange specific biomolecules and support intracellular communication through tuning the permeability of their dynamic bilayer phospholipid membranes. , Permeable nanoshells with subnanometer pores could provide reaction control and selective transport via keeping the membrane structure’s integrity. , As an attractive trigger for permeability control, light provides spatio-temporal precision. Polymersome membranes equipped with azobenzene turned permeable due to the photo-triggered isomerization upon exposure to NIR , and X-ray with sustained diffusion of payloads. However, constant light irradiation was required during the performance period over hours; otherwise, the system slowly reversed to the original impermeable state and suppressed drug release .…”
Section: Introductionmentioning
confidence: 99%